Analisis Kepuasan Wisatawan Telaga Sarangan Magetan Berdasarkan Tourism Experience - Suyono, Bambang (Universitas Merdeka Madiun, 2020)
The research on the Analysis of Tourist Satisfaction of Lake Sarangan Magetan Based on Tourism Experience takes the object of tourists visiting the Sarangan Magetan Lake. This study aims to analyze tourist satisfaction after visiting Sarangan lake tourism objects based on tourism experience and knowing what attributes need to be improved to increase tourist satisfaction. Respondents in this study were tourists who visited the Telaga Sarangan tourist attraction, amounting to 70 people. While the data analysis technique in this study uses the Importance Performance Analysis. The research findings show that (1) Priority factors that need to be improved are novelty indicators with question items. I get new experiences after traveling in Sarangan Lake and (2) Factors that need to be maintained and improved such as comfortable traveling in Sarangan Magetan Lake, tourists feel comfortable and happy when visiting, get an unforgettable experience after visiting, get an unforgettable experience and get new experiences, the beautiful Sarangan Lake Magetan tourist attractions, feel amazed at its beauty.Â Keywordsâ€”: tourist satisfaction; tourism experience.